PLC Konsep, Pemrograman dan Aplikasi (Omron CPM1A/CPM2A dan ZEN Programmable Relay)/ Edisi Pertama - PUTRA, Agfianto Eko (Gava Media, 2004)
PLC Konsep, Pemrograman dan Aplikasi (Omron CPM1A/CPM2A dan ZEN Programmable Relay)/ Edisi Pertama